Integrating social dynamics in the participatory modeling of small-scale cattle farmers’ perceptions and responses to climate variability in the Yucatan Peninsula, Mexico - Pérez-Lombardini, Fernanda; Siqueiros-García, Jesús M.; Solorio-Sánchez, Francisco Javier; Galindo, Francisco (Frontiers in Sustainable Food Systems, 2024)
Extensive livestock production is a vital widespread economic activity for food safety, but it has significant implications for climate change, while also being vulnerable to its effects. In the Mexican tropics, small and medium-sized cattle farmers, which constitute a substantial portion of the national cattle farming sector, are particularly affected by climate change due to rising temperatures and changing rainfall patterns. Despite the unsustainable situation, there are currently no public social programs supporting or promoting the adoption of alternative models, such as silvopastoralism, to address climate change adaptation and vulnerability mitigation. This study aims to understand the factors and interactions between the social, animal and ecological systems within the small-scale cattle socioecosystems in the south region of the Yucatan Peninsula, exploring cattle farmers’ perspectives on climate change, as well as their strategies and responses to extreme events like drought. Using fuzzy cognitive maps as participatory modeling and reflection tool, we found a conceptual gap between climate change and drought, indicating a lack of sustainable adaptive thinking toward these challenges. Interestingly, we found that local social organization, cultural dynamics, and spiritual practices are equally significant factors than technical and environment-oriented changes to the management of ranches in shaping an optimal cattle farming scenario. Our findings reveal that the management of cattle farms involves complex interplay among technical, environmental, social, political, and cultural elements, highlighting the inherent need to consider social values and preferences as fundamental components of sustainability. These factors are being excluded when promoting and studying the adoption of practices that seek sustainable cattle farming. Consequently, this study establishes the initial groundwork for employing participatory modeling with social actors engaged in the small-scale cattle context in Yucatan. The goal is to emphasize the importance of the social dimension in the general management of the small-scale cattle socioecosystem, thus in promoting sustainable cattle farming.